GraphQL server - Blažek, Milan; Blažek Milan (České vysoké učení technické v Praze, 2016)
Práce popisuje technologii GraphQL od společnosti Facebook a vystavuje ji porovnání s tradičním přístupem REST. Implementační část práce využívá právě technologii GraphQL spolu s dalšími souvisejícími knihovnami.

The thesis describes the GraphQL technology by Facebook. This technology is compared with traditional approach REST. Implementation of this work uses GraphQL technology along with other related libraries to demonstrate use in practice.
GraphQL server
Keywords: GraphQL, API, REST, schéma, JSON, komunikace.; GraphQL, API, REST, schema, JSON, communication.